Clima organizacional y su impacto en las actividades secretariales en el Gobierno Autónomo Descentralizado Municipal del Cantón Puebloviejo - Fajardo Santillan, Evelyn Melissa (2020)
The organizational climate is currently a commitment and a shared responsibility among those who manage. An adequate organizational climate can generate greater efficiency in management and satisfaction in performance; For this reason, it is important to generate adequate work environments, so that the management of organizations provides quality services. Analyze the organizational climate and its impact on secretarial activities in the Autonomous Decentralized Municipal Government of the Puebloviejo Canton. For this purpose, a survey was applied to 4 secretaries, 1 interview still in charge of the department. The questionnaire with five interrogations, structured with a Likert-type scale, four alternative answers such as yes, no, sometimes, and always, allowed to obtain the required information. It is concluded that the factors that require particular attention are the outdated knowledge of the electronic equipment, lack of communication, and the demotivation of the research carried out. According to the recommendations and conclusions, it follows that there is no factor management model mentioned above, suggesting strategies that contribute to improve the organizational climate of the institution, and directly affect the perception of its staff.